2017
DOI: 10.1002/jat.3446
|View full text |Cite
|
Sign up to set email alerts
|

Development of haemostatic decontaminants for treatment of wounds contaminated with chemical warfare agents. 3: Evaluation of in vitro topical decontamination efficacy using damaged skin

Abstract: Previous studies have demonstrated that haemostatic products with an absorptive mechanism of action retain their clotting efficiency in the presence of toxic materials and are effective in decontaminating chemical warfare (CW) agents when applied to normal, intact skin. The purpose of this in vitro study was to assess three candidate haemostatic products for effectiveness in the decontamination of superficially damaged porcine skin exposed to the radiolabelled CW agents, soman (GD), VX and sulphur mustard (HD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The latency period between exposure and advanced signs of SM toxicity was also shorter than that reported in studies conducted by Reid and colleagues, in which both the amount of SM applied to the skin (400 μl) and the exposure duration (2 h) were greater than those used in this study (Reid et al ., ). The rapid appearance of these advanced signs of toxicity correlated with an increased rate of absorption in vivo and these data are in agreement with in vitro percutaneous penetration studies (Lydon et al ., ) . This suggests that the latency period between SM exposure and the appearance of symptoms in undamaged skin could be in part due to delayed absorption and not, as previously hypothesised, exclusively by cellular processes such as DNA damage or inflammatory‐mediated responses (Papirmeister et al ., ; Arroyo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The latency period between exposure and advanced signs of SM toxicity was also shorter than that reported in studies conducted by Reid and colleagues, in which both the amount of SM applied to the skin (400 μl) and the exposure duration (2 h) were greater than those used in this study (Reid et al ., ). The rapid appearance of these advanced signs of toxicity correlated with an increased rate of absorption in vivo and these data are in agreement with in vitro percutaneous penetration studies (Lydon et al ., ) . This suggests that the latency period between SM exposure and the appearance of symptoms in undamaged skin could be in part due to delayed absorption and not, as previously hypothesised, exclusively by cellular processes such as DNA damage or inflammatory‐mediated responses (Papirmeister et al ., ; Arroyo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, a product suitable for halting bleeding and decontaminating wounds or abraded skin would be of significant clinical benefit. Previous studies have demonstrated that WoundStat™, a granular haemostat, has comparable efficacy to in‐service military decontaminants (fuller's earth and M291) in the decontamination of both undamaged and damaged skin (Dalton et al ., , Lydon et al ., ). Additionally, WoundStat™ maintains its haemostatic capability in the presence of toxic chemicals, including SM, in vitro (Hall et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In certain cases, there is the potential to inadvertently produce toxic breakdown products, as observed with the degradation of VX (Munro, 1999). A wide range of products have been evaluated for decontamination of surfaces (Capoun, 2014;Yang, 1992); however, few of these are suitable for skin decontamination (Salerno, 2016;Schwartz, 2012;Thors, 2017), especially if the skin is damaged (Dalton, 2017;Lydon, 2017). Given the lack of medical treatments for some chemical contami nants, such as sulphur mustard, decontamination can be used to mitigate toxic effects by reducing the contaminant and…”
Section: Introductionmentioning
confidence: 99%